PENINGKATAN PEMAHAMAN KONSEP GEOMETRI MELALUI TAHAPAN BERFIKIR VAN HIELE DI SMP NEGERI 8 LANGSA - Muliati, Sri (At- Tarbawi, 2020)
Understanding the concept is a benchmark students can proceed to the next stage in the learning process and the stage of thinking Van Hiele is a good solution to direct students to the actual concept of geometry. Stages of thinking Van Hiele specializes in teaching geometry. There are three main elements in teaching geometry, namely time, teaching material, and the teaching methods applied. If the three elements are arranged in an integrated manner, they will be able to improve students' thinking abilities to the higher stages of thinking. The purpose of this study was to determine whether there was an increase in understanding of the geometrical concepts of eighth grade students of SMP Negeri 8 Langsa through the Van Hiele thinking stage. This research was classified into quasi-experimental research. This study uses a One Group Pretest-Posttest Desaign research design. The population in this study were all eighth grade students of SMP Negeri 8 Langsa. Samples were taken using simple random sampling technique and students of class VIII I were selected as sample classes. The instrument of this study is the ability to understand concept tests. This test was arranged in the form of a description consisting of 6 questions. From the results of the calculation of the percentage understanding of students' geometrical concepts showed an increase of 48%. The results of data analysis obtained that count> t table is 12.59> 2.08, this means that Ho is rejected and Ha is accepted, so it can be concluded that there is an increase in understanding of students' geometry concepts through the stages of van hiele thinking at SMP Negeri 8 Langsa.   Keywords: Stages of thinking Van Hiele, Ability to understand concepts and Geometry.